ARM ROBOT PEMINDAH BARANG (AtwoR) MENGGUNAKAN MOTOR SERVO MG995 SEBAGAI PENGGERAK ARM BERBASIS ARDUINO - Andrian Andrian; Reni Rahmadewi; Insani Abdi Bangsa (LPPM Poltek ST Paul, 2020)
The development of increasingly sophisticated technology and industrial growth that is increasingly developing in Indonesia. Along with the rapid development of technology, robotics technology is experiencing a very significant development. Various kinds of research on robotics are continuously being developed to improve the function of robots in helping human work. This robot arm uses Arduino as a system that functions to control the robot's motion in the goods moving robot. And for the Arm robot part, we use the MG995 servo motor, which is as an actuator for the robot arm which will move after processing the data generated by the color sensor. This test is the servo on the robot arm, each rotating, namely servo1 90o, Servo2 360o, servo3 360o, servo4 360o. In the servo 2,3 and 4 it rotates continuously Counter Wise (CW) and Counter Clock Wise (CCW). The results of the test for each servo are carried out using a load of 0 - 700 grams, and the results of the average duration value obtained by each servo are servo1 = 4.12 seconds, servo2 = 4.75 seconds, servo3 = 4.62 seconds, servo4 = 3 second. For the total results of the moving Arm, which is 16.5 seconds, and each experiment results 8 times with an increase of 7 times.